PENGARUH PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR MATEMATIKA MATERI RELASI DAN FUNGSI - Vinsensius Supi; Stefanus Notan Tupen; Stefania Baptis Seto (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2020)
Abstract The purpose of this study was to determine student learning outcomes using the type of jigsaw cooperative learning model for relation and function material in class VIII students of SMPK Swadaya Maukaro in the 2019/2020 academic year. The type of research used is experimental research with a quantitative approach that begins with the preparation of a Learning Implementation Plan (RPP), Student Worksheets (LKS), and Learning Outcomes Test (THB). In this study, the population was all class VIII A students of SMPK Swadaya Maukaro Ende Tahin Ajaran 2019/2020. The sample taken was 20 students of class VIII with the technique used was simple random sampling (simple random technique). Data collected through tests of student learning outcomes. The data analysis technique used is covariance analysis (ANAKOVA) to determine the validity of the author's learning tools using the product-moment correlation formula. The results of the preparation of the type of jigsaw cooperative learning device produce good/valid learning tools. In this case, supported by analysis of covariance (ANAKOVA) with the results obtained by statistical F-count - 15.26179 and F - table- 4.15, it gives a significant value so it can be said that the type of jigsaw cooperative learning can improve student learning outcomes for relation and function material.